PENGUKURAN KINERJA KEUANGAN MENGGUNAKAN BALANCED SCORECARD PADA KOPERASI KPRI OBOR - Farah, Nurul Faradillah; Baiq Anggun Hilendri Lestari; Adithya Bayu Suryantar (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
The purpose of this study is to determine the measurement of performance from a financial perspective (liquidity ratio, solvency ratio, reliability ratio), customer perspective (customer acquisition rate), internal business process perspective (manufacturing cycle efficiency) and learning and growth perspective (employee satisfaction level and employee retention rate) using the Balanced Scorecard method at the Employee Cooperative of the Republic of Indonesia (KPRI) Obor Kota Bima. The population of the study includes 101 active member customers with the sampling technique is accidental sampling with saturated sampling/census method. This study obtained the results that the measurement of financial performance using the Balanced scorecard was assessed from four perspectives, namely the internal business perspective, the customer perspective, and the growth and learning perspective were considered efficient. Meanwhile, the financial perspective measured through three ratios is considered inadequate. KPRI Obor's performance based on the measurement of the balance criteria of the Balanced scorecard, is considered quite good with a score of 0.2 (Quite Good).